2013
DOI: 10.1115/1.4025544
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Predictions of Unsteady Viscous Flows Around Bluff Bodies by Aerodynamic Reduced Order Models

Abstract: This paper describes an efficient reduced order model (ROM) applied in the aerodynamic analysis of bluff bodies. The proposed method, which is based on eigensystem realization algorithm (ERA), uses the impulse response of the system obtained by computational fluid dynamics (CED) analysis to construct a ROM that can accurately predict the response of the system to any arbitrary input. In order to study the performance of the proposed technique, three different geometries including elliptical and rectangular se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Based on this property, as ∑ D includes very small singular values, UDDVDT is negligible compared to URRVRT (Ebrahimnejad et al , 2014b).…”
Section: Constructing Aerodynamic and Aeroelastic Rommentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this property, as ∑ D includes very small singular values, UDDVDT is negligible compared to URRVRT (Ebrahimnejad et al , 2014b).…”
Section: Constructing Aerodynamic and Aeroelastic Rommentioning
confidence: 99%
“…The authors have recently showed the results of ERA-based aerodynamic ROM for a long-span bridge with and without guide vanes (Ebrahimnejad et al , 2012). Also, this procedure has been successfully applied to a bridge section and two simple canonical sections with the same chord length in Ebrahimnejad et al (2014a) and three super long-span bridges in Ebrahimnejad et al (2014b). This work develops the method proposed in Ebrahimnejad et al (2014a, 2012, 2014b) to perform aeroelastic analysis by coupling a pertinent aerodynamic ROM and compatible reduced DOF structural system.…”
Section: Introductionmentioning
confidence: 99%